2021
DOI: 10.1021/acs.langmuir.1c01283
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Modification Degrees on the Colloidal Stability of Amphiphilic Janus Graphene Oxide in Aqueous Solution with and without Electrolytes

Abstract: Colloidal stability of modified graphene oxide (GO) is fundamental for its practical applications. Meanwhile, most of the investigations mainly focused on the nanosheets modified by a certain amount of modifiers and neglected the effects of the modification degree, which could vary the physical and chemical properties of modified GO and significantly affect its stability in solution. To the best of our knowledge, this study initially investigated the impact of modification degrees on the colloidal stability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…The smaller CAs on wax-coated glasses than that on glasses for JANPs illustrate their amphiphilic structures patently, whose one side is more hydrophilic than the opposite side. 36 In addition, the gradually increased CAs of various NPs deposited on glass from HLNPs (∼0°) to JA12C (∼ 127°) further confirm the successful modification to HLNPs, which can also be indicated by the Pickering emulsion experiment (Figure S3).…”
Section: ■ Results and Discussionsupporting
confidence: 57%
“…The smaller CAs on wax-coated glasses than that on glasses for JANPs illustrate their amphiphilic structures patently, whose one side is more hydrophilic than the opposite side. 36 In addition, the gradually increased CAs of various NPs deposited on glass from HLNPs (∼0°) to JA12C (∼ 127°) further confirm the successful modification to HLNPs, which can also be indicated by the Pickering emulsion experiment (Figure S3).…”
Section: ■ Results and Discussionsupporting
confidence: 57%
“…Since the methods used to characterize the hydrodynamic size and ζ-potential of nonspherical nanomaterials treated them as spherical nanoparticles that have the same average translational diffusion coefficients, we therefore used analytical expressions of interaction energy derived for spherical particles in the modeling. The use of sphere–sphere DLVO model for nonspherical nanomaterials has been demonstrated in previous individual studies and satisfactory results were reported. ,, …”
Section: Methodsmentioning
confidence: 77%
“…The varied experimental approach could weaken the validity of the comparison among studies. Rationale for criterion 2 is that the aggregation behavior of coated nanomaterials is largely determined by the properties of the surface coating rather than those of the “bare” nanomaterial. , …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The morphologies of GO, Ch–Trp/GO, and Ch–Met/GO were observed by using high-resolution TEM (Figure ). Figure a,a1 shows the morphologies of GO, where the bending and overlapping of the nanosheets can be observed owing to the hydrogen bonding interactions generated by the functional groups on the GO surface and the π–π stacking of the carbon skeleton . In contrast, the number of edge folds increased in the functionalized GO nanosheets, indicating the increased activity of the modified material.…”
Section: Resultsmentioning
confidence: 99%